Externally controlled drug release using a gold nanorod contained composite membrane. Issue 23 (31st May 2016) - Kim, Kibeom; Jo, Min-Chul; Jeong, Sundo; Palanikumar, L.; Rotello, Vincent M.; Ryu, Ja-Hyoung; Park, Myoung-Hwan
Abstract : Versatile drug delivery devices using nanoporous membranes consisting of gold nanorods and dendrimers have been demonstrated to provide light-triggered on-demand pulsatile release from a reservoir containing highly enriched therapeutics for a real patient's needs. Abstract : Versatile drug delivery devices using nanoporous membranes consisting of gold nanorods and dendrimers have been demonstrated to provide light-triggered on-demand pulsatile release from a reservoir containing highly enriched therapeutics for a real patient's needs. The drug release rate is directly correlated with the temperature increase and irradiated energy of a near-IR laser in both static and fluidic devices. This biocompatible platform for on-demand control was further confirmed by in vitro experiments. Interestingly, different responses to stimuli were obtained from each drug in the absence and presence of NIR light, indicating the versatile potential of our on-demand drug delivery system in less-invasive therapies requiring multi-drug delivery strategies. The enhanced delivery system will improve therapeutic efficacy and reduce side effects through regulation of plasma drug profiles.